PENGEMBANGAN E-FLASHCARD MATERI PANCASILA DALAM KEHIDUPANKU KELAS V SEKOLAH DASAR - Nurhaliza, Siti Nurhaliza; Sukirno; Inge Ayudia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this research found that the use of interactive digital learning media in Pancasila Education learning is still not varied, the role of students is still as recipients of information and learning is still teacher-centered so that student involvement in the learning process is not optimal. This study aims to determine the feasibility of e-flashcard learning media in Pancasila Education learning on the Pancasila in My Life material. This research was conducted at Gampong Teungoh Elementary School. The subject of this research is a type of research and development, namely Research and Development (R&D). The research design used in this study consists of 5 stages, namely the ADDIE model (analysis, design, development, implementation, and evaluation). The data collection technique used a Likert scale. The data collection instrument used a validation questionnaire from material experts, media experts, language experts, teacher response questionnaires, and student response questionnaires. The data analysis techniques used in this study were qualitative and quantitative analysis techniques. The results of the research obtained from the e-flashcard learning media obtained an assessment of 93.33% from material experts with the category